515. Risk Factors for Death, Intubation and Cardiac Arrest among COVID-19 Patients Hospitalized in Eastern North Carolina. (31st December 2020) - Pona, Adrian; Mao, Yuxuan; Jiwani, Rahim A; Afriyie, Felix; Labbe, Jonathan; Younes, Ahmed; Badr, Mai; Fang, Xiangming; Zomorodian, Laila; Lee, Elisabeth; Cook, Paul P
Abstract: Background: Although majority of coronavirus disease 2019 (COVID-19) cases demonstrate mild to asymptomatic disease, COVID-19 can cause serious complications and death. However, risk factors for development of such complications are not well understood. The purpose of this study was to identify risk factors for intubation, cardiac arrest, and death in COVID-19 patients. Methods: A retrospective chart review of COVID-19 subjects was conducted of the first 185 patients for whom we had complete data sets. Subjects were adult inpatients with a confirmed COVID-19 diagnosis who were hospitalized between March and May 2020 at Vidant Medical Center in Greenville, NC. Data including demographics, comorbidities, laboratory results, treatments, and outcomes were collected. Data were analyzed using logistic regression models and receiver operating characteristic curves in SAS 9.4. Results: Of the first 185 subjects hospitalized for COVID-19, 26% of patients were intubated, 9% experienced cardiac arrest, and 17% died. Subjects who required intubation were more likely to exhibit elevated triglycerides, sepsis, acute respiratory distress syndrome (ARDS), acute kidney injury (AKI), elevated troponin levels, altered mental status, leukocytosis, lymphopenia and elevated ferritin ( P < 0.05) (Table 1). Troponin elevation, ARDS, AKI and thrombocytopenia were risks for cardiac arrest ( P < 0.05) (Table 2). Risk of death was increased in those presenting with advanced age, critical or severe disease, lymphopenia or thrombocytopenia, and in those with history of coronary artery disease (CAD) ( P < 0.05) (Table 3). Patients presenting with AKI, elevated Troponin, ARDS, pressor requirements, critical disease, and sepsis were at increased risk of intubation, cardiac arrest, and death ( P < 0.05) (Tables 1–3). Table 1: Top non-ICU related risk factors for intubation ordered by AUC. Table 2: Top risk factors for cardiac arrest ordered by AUC. Table 3: Top risk factors for death ordered by AUC. Conclusion: In this rapidly evolving pandemic, clinician awareness of risk factors for clinically significant outcomes such as intubation and mortality is essential. Assessment of risk factors like those highlighted in this study can aid in clinical decision-making and predicting patient outcomes. As more data becomes available we aim to develop a validated scoring system to assist clinicians in patient care. Disclosures: Paul P. Cook, MD, Contrafect (Grant/Research Support, Scientific Research Study Investigator)Gilead (Grant/Research Support, Scientific Research Study Investigator)Leonard-Meron (Grant/Research Support, Scientific Research Study Investigator)Lilly (Grant/Research Support, Scientific Research Study Investigator)